2017
DOI: 10.3856/vol45-issue3-fulltext-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, size range and growth rates of hawksbill turtles at a major foraging ground in the eastern Pacific Ocean

Abstract: ABSTRACT.Hawksbill sea turtles (Eretmochelys imbricata) inhabiting the eastern Pacific Ocean are one of the world's most threatened marine turtle management units. Despite the fact that knowledge about the status of sea turtles at foraging grounds is a key element for developing the effective conservation strategies, comprehensive studies of hawksbills at foraging habitats in the eastern Pacific remain lacking. For many years anecdotal information indicated Coiba Island National Park in Panama as a potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
23
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 23 publications
9
23
0
12
Order By: Relevance
“…All hawksbills were captured in waters of 7 m or shallower. This pattern has been reported for other sites in the EP (Diez et al, 2003;Gaos et al, 2012aGaos et al, , 2016Carrión et al, 2013;Llamas et al, 2017), indicating that they live in shallow areas, likely related to food availability, with greater food densities and diversity in shallow waters (Meylan, 1988;León & Bjorndal, 2002;Carrión et al, 2013).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…All hawksbills were captured in waters of 7 m or shallower. This pattern has been reported for other sites in the EP (Diez et al, 2003;Gaos et al, 2012aGaos et al, , 2016Carrión et al, 2013;Llamas et al, 2017), indicating that they live in shallow areas, likely related to food availability, with greater food densities and diversity in shallow waters (Meylan, 1988;León & Bjorndal, 2002;Carrión et al, 2013).…”
Section: Discussionsupporting
confidence: 73%
“…This is the first study to combine oesophageal lavage and stable nitrogen and carbon isotope analyses in eastern Pacific sea turtles, and to our knowledge is also the first-ever published stable isotope study for hawksbills in this region. The information obtained in this research contributes to the knowledge of the foraging behaviour and general biology of hawksbills (Gaos et al, 2012b;Carrión et al, 2013;Heidemeyer et al, 2014;Chacón et al, 2015;Llamas et al, 2017), and our data show that coastal waters of Golfo Dulce offer important shelter and food for this critically endangered species Carrión et al, 2013). Moreover, the hawksbill's apparent fidelity to this area-as evidenced by numerous recapturesunderscores the need to protect the habitats and prey resources present in Golfo Dulce (Chacón et al, 2015).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Traditionally, the main focus of research in marine turtles has been on nesting beaches (Bjorndal 1999). Yet, long-term studies in foraging areas have contributed to our knowledge on the general foraging ecology of marine turtles , Bjorndal et al 2000, Meylan et al 2011, and more recent studies have focussed on patterns of recruitment, how much time turtles spend in these areas and at what age and size they are expected to reach maturity and leave those habitats (Krueger et al 2011, Patrício et al 2011, Bell & Pike 2012, Colman et al 2015, Llamas et al 2017. There is still a need, however, for a more complete understanding of immature life stages, including population dynamics, survival rates and habitat use (Rees et al 2016, Wildermann et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies revealed new foraging habitats. Llamas et al (2017) The third group of studies focused on several of the long-standing anthropogenic threats facing sea turtle: incidental catch (also known as bycatch) and illegal take (Wallace et al, 2011). Liles et al (2017) investigated the impact of the lobster gillnet fishery in Central America and estimated one of the highest rates of gillnet bycatch and mortality for hawksbill turtles anywhere in the world.…”
mentioning
confidence: 99%